Leading to the 2003 Iraq War - Nikolaev, Alexander G. author. aut Link
VII, 283 p.
Keywords: A telling analysis of the pre-war media debate around the globe which set the stage for the 2003 Iraq war. By concentrating on the pre-war coverage, this group of scholars engages in a more open discussion of the issues than would take place during wartime, and uncovers the implications for each country's position on international concerns.